A new species of the genus Ptochoryctis Meyrick, 1894 (Lepidoptera: Autostichidae) from India - Sterling, Mark. J.; Singh, Navneet (Zootaxa, 2025)
Ptochoryctis sundarbanica sp. nov. is described from two adult specimens found in degraded mangrove habitat in the Sundarbans, West Bengal, India.